Schools and New Learning Spaces in Milan. An Educational Experience - António Carvalho; Szymon Ruszczewski; Filippo Piscioli (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The article reflects on recent models for pedagogy and their impact on educational space, from an architectural design point of view. It starts by framing the present-day situation of the existing schools in Milan, built under legal requirements from the 1970s, resulting today in a great number of obsolete educational facilities.Recent programs and educational policies, both at national and local levels, are presented to frame the new programme “Inventing Schools,” a collaborative partnership between the Municipality and the Politecnico di Milano. The goal is to explore and apply these pedagogical models to the design of new educational facilities in Milan, thereby intended to replace or refurbish the (now) problematic old schools.Dealing with second year students of the Bachelor Programme in Architecture, the primary school at Via Massaua was selected for their project. The student design proposals are approached by exploring the link between the school and the public space, the school and the neighbourhood, and the school and the street. The students considered different pedagogical models translated into spaces, confronting them with theoretical models and reference case studies, ultimately contributing to the discussion surrounding the school of the future.The project experiences explore the possible forms and organisation of spaces, so that the school becomes a centre open to the inhabitants of the district, and a space for learning about society and the city. This requires a clear articulation between safety solutions designed to protect the very young pupils, while providing coherent and autonomous access to adults and other users from the community, so as to share the cultural and sporting facilities of the school. This avoids double investments from the municipality and, of paramount importance, strengthens the sense of sharing and belonging to a social community.